Acromegaly - dealing with an uncooperative patient - Michał Obel; Ewelina Mazurek; Adrian Kuś; Małgorzata Szypłowska; Adrianna Gorecka; Bartłomiej Zaremba (Kazimierz Wielki University, 2020)
Introduction: Acromegaly is a chronic disease resulting from increased secretion of growth hormone. The main reason of elevated GH concentration is pituitary adenoma that originates from somatotropic cells. As a consequence, several changes in the organism appear such as progressive deformation of the skeleton with enlargement of the skull, hands and feet, growth of soft tissues, bones and internal organs as well as many other systemic complications which are responsible for increased mortality in untreated patients.   Case report: A 60-year-old patient was diagnosed with acromegaly due to the pituitary macroadenoma and associated hypopituitarism in the thyroid and gonadotropic axis 4 years ago. The disease was suspected in April 2016 by a rheumatologist, and then confirmed on the basis of hormonal tests in the Endocrinology Clinic (IGF1 - 754.7 ng/ml, N: 77-224; GH - 2.51 ng/ml, no inhibition in OGTT). The imaging examination revealed a pituitary macroadenoma with dimensions of 17x15x19 mm. The medical history revealed the characteristic symptoms of acromegaly like enlargement and deformation of the fingers, enlarged nose, excessive sweating and headaches for the last 12 years. There have been several studies investigating the complications of acromegaly that found abnormalities in the cardiovascular system, metabolic disorders (dyslipidemia, abnormal fasting glycaemia), arthropathies, sigmoid polyps and nodular goiter. Due to the patient's lack of consent to the surgical intervention, treatment with a somatostatin analogue was introduced. During 2-year therapy, the normalization of IGF-1 concentration was not achieved. In October 2018 patient completely abandoned therapy with somatostatin analogue. In 2019 the lack of control of acromegaly was confirmed. During hospitalization in 2020 the uncontrolled acromegaly was stated once again. The patient still does not consent to the surgical procedure to remove pituitary macroadenoma, however, he agreed for systematic re-treatment with a somatostatin analogue.   Conclusions: Isolated pharmacological treatment doesn't always allow for sufficient control of an illness. Effective treatment of acromegaly should consist of surgery as well as conservative treatment. The introductinon of both 2nd generation analogues and GH receptor antagonists in therapeutic programs makes effective pharmacological treatment possible.